Correcting the Arcjet Thruster Disturbance in GOES‐16 Magnetometer Data - S. Califf; D. Early; M. Grotenhuis; T. M. Loto'aniu; J. Kronenwetter (Space Weather)
Abstract The GOES‐R series magnetometers provide observations of the Earth's magnetic field at geostationary orbit for operational use by National Oceanic and Atmospheric Administration (NOAA)'s Space Weather Prediction Center. The GOES‐R spacecraft use arcjet thrusters for orbital stationkeeping, and the partially ionized thruster plume creates a relatively large (~20 nT) disturbance in the magnetometer data. This study presents a correction algorithm that removes the arcjet signal from the magnetometer data. The algorithm is based on an observed linear relationship between the arcjet disturbance and the ambient magnetic field. We estimate correction parameters using data from GOES‐16 (the first spacecraft of the GOES‐R series), evaluate the uncertainties in the corrected data during arcjet events, and discuss limitations and considerations for arcjet correction in the GOES‐R series magnetometers.